2020
DOI: 10.1093/icvts/ivaa183
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics of internal mammary artery–left anterior descending artery anastomoses

Abstract: OBJECTIVES The aim of this study was to elucidate the remodelling of the internal mammary artery (IMA)–left anterior descending artery anastomosis and compare 2 different anastomosis techniques (end-to-side versus side-to-side) using computational fluid dynamics. METHODS This study included 9 patients. Computed tomography (CT) angiography was performed immediately after coronary artery bypass grafting (CABG) and at 3–6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Kanzaki et al reported that there was no significant difference in bypass blood flow between end-to-side anastomosis and side-to-side anastomosis using CFD. 17) In this study, all anastomoses were performed by sideto-side anastomosis, and Case 2 was selected because of its favorable OSI and TTFM values. By selecting the case with the most stable anastomotic conditions, it was possible to remove the bias due to anastomotic factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kanzaki et al reported that there was no significant difference in bypass blood flow between end-to-side anastomosis and side-to-side anastomosis using CFD. 17) In this study, all anastomoses were performed by sideto-side anastomosis, and Case 2 was selected because of its favorable OSI and TTFM values. By selecting the case with the most stable anastomotic conditions, it was possible to remove the bias due to anastomotic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Kanzaki et al reported that there was no significant difference in bypass blood flow between end-to-side anastomosis and side-to-side anastomosis using CFD. 17) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation